2008
DOI: 10.1080/02786820802209129
|View full text |Cite
|
Sign up to set email alerts
|

Measurements and Factorial Analysis of Micron-Sized Particle Adhesion Force to Indoor Flooring Materials by Electrostatic Detachment Method

Abstract: Airborne concentration of micron-sized particulate matter (PM) is an important index of indoor air quality. While human activity is considered the main reason causing indoor particle resuspension, theoretical particle adhesion force models give predictions of adhesion force much larger than the disturbance forces introduced by human activity. This work suggests that the imperfect contact between particles and surfaces can greatly reduce the adhesion bond. Electrostatic detachment method is used to measure the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…For resuspension from flooring, airflow associated with the downward foot motion is likely very impulsive with high acceleration (Khalifa and Elhadidi 2007). Resuspension due to human activity may also generate additional removal forces, such as mechanical forces, due to surface vibrations, and electrostatic forces associated with the walking process (Gomes et al 2007;Hu et al 2008;Qian and Ferro 2008). The impact of airflow acceleration, turbulence levels, and additional removal mechanisms were not considered in this investigation, although these variables may have significant impact on resuspension under real conditions in the indoor environment.…”
Section: Limitations Of the Present Investigationmentioning
confidence: 99%
“…For resuspension from flooring, airflow associated with the downward foot motion is likely very impulsive with high acceleration (Khalifa and Elhadidi 2007). Resuspension due to human activity may also generate additional removal forces, such as mechanical forces, due to surface vibrations, and electrostatic forces associated with the walking process (Gomes et al 2007;Hu et al 2008;Qian and Ferro 2008). The impact of airflow acceleration, turbulence levels, and additional removal mechanisms were not considered in this investigation, although these variables may have significant impact on resuspension under real conditions in the indoor environment.…”
Section: Limitations Of the Present Investigationmentioning
confidence: 99%
“…In order for resuspension to occur, the adhesion force binding the substrate and particles must be overcome (Corn 1961). Hu et al (2008), in their measurements of adhesion forces between 1 µm alumina particles and bacterial spores and vinyl and rubber indoor flooring materials, found the actual area of contact between particles and surfaces is less than the theoretically ideal contact area for indoor surfaces. Differences in substrates, particularly microscale surface roughness, are therefore likely to affect resuspension.…”
Section: Discussionmentioning
confidence: 99%
“…Full-scale walking-induced resuspension studies have reported resuspension from both monolayer (Karlsson et al 1999;Tian et al 2011) and multilayer deposits Kubota et al 2009;Tian et al 2011;Shaughnessy andVu 2012, Kubota andHiguchi 2013) on hard flooring. Gomes et al (2007) found aerodynamic removal forces associated with airflow disturbances generated by human walking to be the primary mechanism for particle resuspension from flooring, although surface vibrations, mechanical abrasion, and electrostatic forces can contribute to resuspension (Gomes et al 2007;Hu et al 2008;Qian and Ferro 2008;Hubbard et al 2012). Several studies investigated the airflow generated by foot motions.…”
Section: Hard Flooringmentioning
confidence: 99%